PROTOTIPE DINDING BETIK HASIL DAUR ULANG SAMPAH PLASTIK - SRI RESPATI NURCAHYANINGSIH; KUSUMO DRADJAD SUTJAHJO; DJEDJEN ACHMAD (Jurnal Poli-Teknologi, 2013)
Researches about plastic concrete(betik)have been done since 2004 by kusumo drajad s. Betik consistsof a mixture of cement, sand, plastic aggregates (pellets) and water, can be categorized as lightweight concrete which have the same compressive strength with the normal concrete, approximately 120 kg/cm2. The research prototype betik walls which is done today as the result of the development composision ofbetik , consist of 1portion of cement, 2 portions of sand and 4 portions of plastic aggregate (recycling product ) and 0,6 portion of water. Afterward, all materials were mixed and poured into plastic bottles of mineral water packaging (such as aqua, ades ). Before the bottles are filled in,it should be cut into24 cm high, assembled with bendrat wires, and added concrete steel reinforcement diameter of 8 mm at the center of the bottle into a series of blocks that consisting of 6 bottles. Based on the testing in physical properties of a block betik’s wall samples have been tested: the slump’s average value is 6cm, the bottom’s surface is quite smooth, no cracked and all intact, but there are several cross-section of bottle that has been filled betik not circle.the experiment also showed: the size of betik’s block : 8.5 cm widht, 48 cm length, 24 cm high and average weight of each block betik’s walls is 9.5 kg. Furthermore, the blocks of betik’s wall were arranged and bonded using mortar that has composition 1 portion of cement and 4 portions of sand. The block of betik’s wall also supported horizontally by using bendrat wire and vertically by using 8 mm concrete bar, and shaped a segment of betik’s wall into 1.5 x 1.5 m. Subsequently, the wall of segment was standed up and than taken off, so the wall collapsed. The results shown that the knots of bindrat or concrete bar were in good condition and didn’t fall. The other results in this study were the blocks of betik’s wall blocks that collapsed are still in whole condition and it can be used again. Keywords: betik, plastic pellets, walls, concrete